REXUS-4: Vehicle And Subsystems Design, Flight Performance and Experiments - Stamminger, Andreas; Czech, Manuel; Griebel, Hannes; Hörschgen, Marcus; Persson, Olle; Pinzer, Markus; Rießelmann, Jens; Shavsavar, Amin (ESA Communication Production Office, 2009)
On the 22nd of October 2008 EuroLaunch launched the REXUS-4 rocket at Esrange in Northern Sweden. EuroLaunch is a joint venture of the DLR Mobile Rocket Base and the SSC Esrange Space Center. The REXUS-4 payload was comprised of five technological experiments from German and Swedish Universities. The REXUS-4 mission was also the maiden flight of a newly developed service system. After this successful demonstration, it has been implemented into the REXUS/BEXUS programme. This paper gives a short overview on the development of the REXUS service system and points out the advantages of using standard interfaces for student experiments. Furthermore it will contain a description of the REXUS-4 vehicle, the mission, the campaign and the experiments.